2012 13th International Workshop on Cellular Nanoscale Networks and Their Applications 2012
DOI: 10.1109/cnna.2012.6331463
|View full text |Cite
|
Sign up to set email alerts
|

An Associative Memory with oscillatory CNN arrays using spin torque oscillator cells and spin-wave interactions architecture and End-to-end Simulator

Abstract: An Associative Memory is built by three consecutive components: (1) a CMOS preprocessing unit generating input feature vectors from picture inputs, (2) an AM cluster generating signature outputs composed of spintronic oscillator (STO) cells and local spin-wave interactions, as an oscillatory CNN (O-CNN) array unit, applied several times arranged in space, and (3) a classification unit (CMOS). The end to end design of the preprocessing unit, the interacting O-CNN arrays, and the classification unit is embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…In practice, associative memory processors are important building blocks for applications such as pattern recognition and, in general, classification. These considerations, combined with the tiny size and frequency tunability of spin-torque oscillators, have motivated the proposal of associative memory hardware based on arrays of interacting harmonic spin-torque nano-oscillators [110] [111]. It has been shown that these systems can be decomposed in clusters of reasonable size for the arrays of synchronized spin-torque oscillators without performance degradation [112].…”
Section: Spin-torque Nano-oscillators As Neuronsmentioning
confidence: 99%
“…In practice, associative memory processors are important building blocks for applications such as pattern recognition and, in general, classification. These considerations, combined with the tiny size and frequency tunability of spin-torque oscillators, have motivated the proposal of associative memory hardware based on arrays of interacting harmonic spin-torque nano-oscillators [110] [111]. It has been shown that these systems can be decomposed in clusters of reasonable size for the arrays of synchronized spin-torque oscillators without performance degradation [112].…”
Section: Spin-torque Nano-oscillators As Neuronsmentioning
confidence: 99%
“…A possible solution to these issues could be the synchronization of a few STNOs [6,19,21,22,26,28]. Synchronization among multiple auto-oscillators can also be useful in the framework of developing associative memories architectures [29][30][31][32]. Previous studies reported on synchronization of STNOs interacting with others via spin waves [25,26,33], exchange coupling [6], electric currents [3,28,34], noisy current injection [19], or via magnetodipolar interaction [21,22,[35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 97%
“…SSNOs exhibit interesting dynamical properties -for example, synchronization [19][20][21] and pattern formation [22][23][24][25] can result when they are coupled together. Biological phenomena such as the synchronized flashing of fireflies [26], circadian rhythms [27,28] and epilepsy [29] result from the interaction of SSNOs, while coupled systems of SSNOs have been shown to have image processing capabilities [24,30] and have been proposed for associative memories [31,32]. In this paper, we first review recent work that establishes that SSNOs can also serve as substrates for general-purpose Boolean computation.…”
Section: Introductionmentioning
confidence: 99%